Candi Kedaton, Sejerah, Struktur dan Potensi sebagai sumber belajar di SMA - Alfarizi, Moh; Maryati, Tuty; Arta, Ketut Sedana (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This research aims to 1) investigate the history of Kedaton Temple in Andungbiru Village, Tiris Sub-district, Probolinggo Regency, 2) understand the structure of Kedaton Temple in Andungbiru Village, acknowledging that Kedaton Temple possesses a rich historical heritage, and 3) explore the potential of Kedaton Temple's history as a learning resource for high school history education. In this study, the researcher employs a qualitative descriptive approach with data collection methods including observation, interviews, and document/content analysis, using purposive sampling and snowball sampling techniques. The types of data used are divided into two categories: primary data and secondary data. The research results include: 1) there is a wealth of local history, architectural art, and cultural values contained within Kedaton Temple, 2) providing an in-depth view of the structure of Kedaton Temple, and 3) offering a learning resource that can enrich the educational experience of high school students. This also aims to strengthen their understanding of the cultural heritage in their surroundings. Keywords: Kedaton Temple, History, Structure and History Learning Resourse